Espaces et processus de politisation de l’humanitaire. L’Armenian Relief Fund et le National Armenian Relief Committee (1895-1896) : un miroir transatlantique ? - Stéphanie Prévost (Transatlantica)
This article proposes an entangled history of the two main relief funds operating in the United States (the National Armenian Relief Committee, NARC) and Britain (the Armenian Relief Fund, ARF) on behalf of Ottoman Armenians in the context of the 1894-1896 Hamidian Massacres. With the additional input of transnational studies, it posits dissymmetric relations between the ARF and the NARC depending on space (transatlantic / national v. Ottoman / transnational) and time (political time in both the United States and Britain, and stages of the Armenian question). The study also investigates how Anglo-American cooperation between in loco actors distributing relief on behalf of the NARC and the ARF (especially American missionaries, British private agents and consuls) could best develop on the margins of British and American metropolitan spaces; but it also insists that it required a facilitator: here, British ambassador at Constantinople Sir Philip Currie. The article finally contends that Currie’s coordination of the transnational / international relief movement does not only shed light on the Anglo-American collaboration, but more broadly interrogates the widespread understanding that the genesis of humanitarian diplomacy was primordially a consequence of World War One.